La-Fe-Si-based magnetic refrigeration material and preparation method thereof

Through the sintering and heat treatment of spherical La-Fe-Si-based alloy powder and Ag powder, a microstructure of Ag-rich La-Fe-Si particles is formed, which solves the problem of easy cracks in the material, improves the mechanical properties and magneto-thermal effects, and maintains the Thermal conductivity extends the service life of the material.

CN119132769APending Publication Date: 2024-12-13NINGBO INST OF MATERIALS TECH & ENG CHINESE ACAD OF SCI
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411268628.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

La-Fe-Si-based magnetic refrigeration materials are prone to cracks during service, affecting their cycle stability. The prior art resin or metal composite methods will reduce the thermal conductivity of the material or are not conducive to the improvement of magneto-thermal effects.

Method used

The spherical La-Fe-Si-based alloy powder and Ag powder are mixed with sintering, and spherical powder is prepared by aerosolization method, and discharge plasma sintering and heat treatment are carried out to form a microstructure of Ag-rich La-Fe-Si particles wrapped in Ag phase, combined with Hydrogenation is used to improve the mechanical properties and magneto-thermal effects of the material.

Benefits of technology

The mechanical properties and magneto-thermal effects of La-Fe-Si-based magnetic refrigeration materials are improved, while maintaining thermal conductivity and extending the service life of the material.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119132769A_ABST
    Figure CN119132769A_ABST
Patent Text Reader

Abstract

The invention discloses a La-Fe-Si-based magnetic refrigeration material and a preparation method thereof.The preparation method comprises the following steps that S1, spherical La-Fe-Si-based alloy powder and spherical Ag powder are mixed, and mixed powder is obtained; s2, sintering the mixed powder obtained in the step S1 into a block; and S3, the block obtained in the step S2 is subjected to heat treatment, and the La-Fe-Si-based magnetic refrigeration material is obtained. According to the method, the Ag element with the small solid solubility with the iron phase is selected and mixed with the La-Fe-Si-based alloy powder, sintering is carried out, a microstructure with La-Fe-Si particles wrapped with the Ag-rich phase is obtained, and the mechanical property of the material is improved advantageously; besides, the selected spherical La-Fe-Si-based alloy powder is beneficial for ensuring the magnetocaloric effect of the material, and meanwhile, the solid solubility of Ag in an alpha-Fe phase is relatively small, so that a large amount of Ag cannot be dissolved in a matrix in the sintering and heat treatment processes, and the excellent magnetocaloric effect can be obtained.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of magnetic refrigeration materials, and in particular to a La-Fe-Si based magnetic refrigeration material and a preparation method thereof. Background Art

[0002] Magnetic refrigeration technology is a new type of refrigeration method based on the magnetocaloric effect of solid magnetic materials. Compared with the currently commonly used gas compression refrigeration method, the refrigerant in magnetic refrigeration technology is solid, which will not produce a greenhouse effect and is more environmentally friendly. In addition, the theoretical refrigeration efficiency of this technology can reach ~60% of the ideal Carnot cycle, which is much higher than the gas compression refrigeration method. It is one of the ideal alternatives to gas compression refrigeration in the future. At present, researchers have discovered a variety of magnetic refrigeration materials, such as Gd, Gd-Si-Ge, La-Fe-Si, Mn-Fe-P-As and other systems, among which NaZn 13 The La-Fe-Si based alloy with this structure has the characteristics of large magnetocaloric effect, easy adjustment of Curie temperature, no toxic elements and low cost. It is currently recognized internationally as one of the most promising magnetic refrigeration materials.

[0003] La-Fe-Si is an intermetallic compound with significant intrinsic brittleness. The uneven stress to which the material is subjected when repeatedly entering and exiting the magnetic field during service can easily cause cracks in the material. At the same time, the magnetic phase change induced by repeated addition and demagnetization of the material is accompanied by obvious volume changes, which can also cause cracks in the material and worsen the cyclic stability of the material. The prior art proposes to use resin or metal composite methods to solve the above problems. However, the presence of resin will significantly reduce the thermal conductivity of the magnetic refrigeration material, which is not conducive to improving the efficiency of magnetic refrigeration. In the metal composite method, La-Fe-Si quick-setting sheets are first heat-treated to obtain a magnetocaloric phase, and then composited with other low-melting-point metals. The La-Fe-Si particles in this method are mostly irregular in shape, which is not conducive to improving the magnetocaloric effect. Summary of the invention

[0004] In view of the deficiencies of the prior art, the technical problem to be solved by the present invention is how to improve the mechanical properties of La-Fe-Si based magnetic refrigeration materials while maintaining their thermal conductivity and magnetocaloric effect.

[0005] To achieve the above object, the present invention provides a method for preparing a La-Fe-Si based magnetic refrigeration material, comprising the following steps:

[0006] S1, mixing spherical La-Fe-Si based alloy powder and spherical Ag powder to obtain mixed powder;

[0007] S2, sintering the mixed powder obtained in step S1 into a block;

[0008] S3. Heat-treating the block obtained in step S2 to obtain a La-Fe-Si based magnetic refrigeration material.

[0009] The present invention selects Ag elements with relatively low solid solubility in the iron phase and La-Fe-Si based alloy powder for mixing, and performs sintering to obtain a microstructure in which the Ag-rich phase wraps the La-Fe-Si particles, which is beneficial to improving the mechanical properties of the material; in addition, the selection of spherical La-Fe-Si based alloy powder is beneficial to ensuring the magnetocaloric effect of the material, and at the same time, Ag has a relatively low solid solubility in the α-Fe phase, so it will not be dissolved in a large amount in the matrix during sintering and heat treatment, which is beneficial to obtaining an excellent magnetocaloric effect.

[0010] Furthermore, the preparation method further comprises step S0, preparing La-Fe-Si based alloy powder by gas atomization method. The La-Fe-Si based alloy powder is prepared by gas atomization method to ensure the regularity of its shape, which is conducive to forming a microstructure of Ag phase encapsulating La-Fe-Si particles, improving the plasticity of the material, and ensuring the magnetocaloric effect of the material.

[0011] Furthermore, in step S1, the powder diameter of the La-Fe-Si based alloy powder is 0.1-100 μm, and the powder diameter of the Ag powder is 0.1-100 μm. Powders with smaller particle sizes are selected to ensure the coating effect of Ag on La-Fe-Si particles.

[0012] Furthermore, in step S1, the mass proportion of Ag powder in the mixed powder is 5% to 20%. The mass proportion of Ag powder is limited to ensure the Ag phase coating effect and reduce the influence of Ag phase on the magnetocaloric properties of the material.

[0013] Furthermore, in step S2, the sintering method is spark plasma sintering.

[0014] Furthermore, in step S2, the sintering temperature is 650-850°C, the sintering time is 3-10 min, and the sintering pressure is 20-50 MPa. The sintering method can directly sinter the mixed powder without forming before sintering, thereby ensuring the coating effect of the Ag phase during the sintering process.

[0015] Furthermore, in step S3, the heat treatment is carried out under the protection of an inert atmosphere, the heat treatment temperature is 600-1000°C, and the heat treatment time is 5min-6h. The sintered block is subjected to a short-term heat treatment to obtain NaZn 13 Main phase.

[0016] Furthermore, the preparation method further comprises step S4, hydrogenating the material obtained in step S3, wherein the hydrogen pressure is 1 to 5 bar, the treatment temperature is 100 to 500° C., and the treatment time is 1 to 10 hours. Hydrogenation can eliminate internal defects of the material and improve mechanical properties.

[0017] In summary, compared with the prior art, the present invention has the following beneficial effects:

[0018] (1) The composite of La-Fe-Si powder and Ag powder of the present invention obtains Ag-rich phase-wrapped brittle La-Fe-Si particles, which is beneficial to improving the plasticity of the material without destroying the thermal conductivity of the material.

[0019] (2) The raw material powders used in the present invention are all spherical in structure. Compared with irregular powders, the magnetocaloric effect of the materials can be guaranteed after compounding.

[0020] (3) The Ag selected in the present invention has a low solid solubility in the α-Fe phase in the La-Fe-Si powder, so the diffusion of the Ag element during heat treatment and sintering is limited and will not significantly affect the magnetocaloric effect of the material. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 This is a microstructure diagram of the La-Fe-Si based magnetic refrigeration material in Example 1 of the present invention.

[0022] Figure 2 This is a microstructure diagram of the La-Fe-Si based magnetic refrigeration material in Example 2 of the present invention.

[0023] Figure 3 This is a microstructure diagram of the La-Fe-Si based magnetic refrigeration material in Example 3 of the present invention. DETAILED DESCRIPTION

[0024] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0025] It should be understood that the terms described in the present invention are only for describing special embodiments and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. Each smaller range between the intermediate value in any stated value or stated range and any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.

[0026] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention without departing from the scope or spirit of the present invention. Other embodiments obtained from the present invention description will be apparent to those skilled in the art.

[0027] A specific embodiment of the present invention provides a La-Fe-Si based magnetic refrigeration material, which uses spherical Ag powder and spherical La-Fe-Si based alloy powder as raw materials, mixes and sinters to obtain a microstructure in which La-Fe-Si particles are wrapped by an Ag-rich phase, thereby improving the mechanical properties of the La-Fe-Si based magnetic refrigeration material while maintaining its thermal conductivity and magnetocaloric effect.

[0028] The specific steps of the preparation method of La-Fe-Si based magnetic refrigeration material are as follows:

[0029] S0. A spherical La-Fe-Si based alloy powder is prepared by a gas atomization method, and a powder with a diameter of 0.1 to 100 μm is selected as a raw material powder.

[0030] S1. Prepare spherical Ag powder with a diameter of 0.1 to 100 μm, weigh La-Fe-Si based alloy powder and Ag powder according to a set amount, and mix the two evenly to obtain a mixed powder. In a specific embodiment, the mass proportion of Ag powder in the mixed powder is preferably 5% to 20%.

[0031] S2, sintering the mixed powder into a block by spark plasma sintering, during which the Ag phase wraps the La-Fe-Si particles. In a specific embodiment, the sintering process parameters are as follows: sintering temperature is 650-850° C., sintering time is 3-10 min, and sintering pressure is 20-50 MPa.

[0032] S3, heat-treating the block, the heat treatment is carried out under the protection of an inert atmosphere, and obtaining NaZn 13 The main phase is La-Fe-Si based magnetic refrigeration material. In a specific embodiment, the heat treatment temperature is 600-1000° C., and the heat treatment time is 5 min-6 h.

[0033] S4, hydrogenating the obtained material to make its Curie temperature near room temperature, and obtaining hydrogenated La-Fe-Si based magnetic refrigeration material. In a specific embodiment, the hydrogenation process is as follows: hydrogen pressure is 1-5 bar, treatment temperature is 100-500° C., and treatment time is 1-10 hours.

[0034] The above method selects Ag and La-Fe-Si spherical powders with low solid solubility in the iron phase and mixes them, and then sintering them to obtain a microstructure in which the Ag-rich phase wraps the La-Fe-Si particles, which is beneficial to improving the mechanical properties of the material. In addition, the use of La-Fe-Si based alloy powder is beneficial to ensuring the magnetocaloric effect of the material. At the same time, Ag has a low solid solubility in the α-Fe phase, so it will not be dissolved in the matrix in large quantities during sintering and heat treatment, which is beneficial to obtaining excellent magnetocaloric effect.

[0035] The technical solutions and effects of the present invention are illustrated below in conjunction with specific embodiments.

[0036] Example 1

[0037] In this embodiment, La-Fe-Si based magnetic refrigeration material is prepared by the following method:

[0038] (1) The nominal composition of La was prepared by aerosolization 0.6 Ce 0.4 Fe 11.6 Co 0.9 Si 1.6 Spherical powder, wherein the powder with a diameter less than 15 μm is selected as raw material powder;

[0039] (2) Weigh the above powder and Ag powder with a diameter of 10 μm, wherein the mass proportion of Ag powder is 5%, and then place the two powders in a powder mixer and mix them evenly;

[0040] (3) The mixed powder was placed in a Φ15 mm graphite mold, and then sintered in a spark plasma sintering furnace with a sintering pressure of 40 MPa, a heating rate of 100 °C / min, a sintering temperature of 800 °C, and a sintering time of 5 min. After the sintering was completed, the mixture was cooled in the furnace;

[0041] (4) The surface of the sintered sample was polished and cleaned, then sealed in a glass tube with argon protection, heat treated at 800°C for 30 min, and then quenched in water;

[0042] (5) The heat-treated sample was hydrogenated at 300°C for 5 h with a hydrogen pressure of 2 bar.

[0043] The microstructure of the La-Fe-Si based magnetic refrigeration material after sintering in this embodiment is as follows: Figure 1 As shown, the bright area is the Ag-rich phase, and the spherical particles are La-Ce-Fe-Co-Si particles. It can be seen that this method obtains a structure in which the Ag phase wraps the La-Ce-Fe-Co-Si particles, which is beneficial to improving the mechanical properties of the material.

[0044] Example 2

[0045] The difference between this embodiment and embodiment 1 is that the mass proportion of Ag powder in step (2) is 10%, and the other steps and process parameters are the same as those in embodiment 1.

[0046] The microstructure of the La-Fe-Si based magnetic refrigeration material after sintering in this embodiment is as follows: Figure 2 As shown, a structure in which the Ag phase wrapped the La-Ce-Fe-Co-Si particles was obtained.

[0047] Example 3

[0048] The difference between this embodiment and embodiment 1 is that the mass proportion of Ag powder in step (2) is 15%, and the other steps and process parameters are the same as those in embodiment 1.

[0049] The microstructure of the La-Fe-Si based magnetic refrigeration material after sintering in this embodiment is as follows: Figure 3 As shown, a structure in which the Ag phase wrapped the La-Ce-Fe-Co-Si particles was obtained.

[0050] Example 4

[0051] In this embodiment, La-Fe-Si based magnetic refrigeration material is prepared by the following method:

[0052] (1) Preparation of LaFe with nominal composition by gas atomization 11.6 Si 1.4 Spherical powder, select powder with a diameter of 15 to 53 μm as raw material powder;

[0053] (2) Weighing the above powder and Ag powder with a diameter of 15 to 53 μm, wherein the weight proportion of Ag powder is 10%, and then placing the two powders in a powder mixer and mixing them evenly;

[0054] (3) The mixed powder was placed in a Φ15 mm graphite mold, and then sintered in a spark plasma sintering furnace with a sintering pressure of 40 MPa, a heating rate of 100 °C / min, a sintering temperature of 750 °C, and a sintering time of 10 min. After sintering, the mixture was cooled in the furnace;

[0055] (4) The surface of the sintered sample was polished and cleaned, then sealed in a glass tube with argon protection, heat treated at 900 °C for 30 min, and then quenched in water;

[0056] (5) The heat-treated sample was hydrogenated at 300°C for 5 h with a hydrogen pressure of 2 bar.

[0057] Example 5

[0058] In this embodiment, La-Fe-Si based magnetic refrigeration material is prepared by the following method:

[0059] (1) Preparation of LaFe with nominal composition by gas atomization 11.0 Co 0.8 Si 1.2 Spherical powder, select powder with a diameter of 20 to 100 μm as raw material powder;

[0060] (2) Weighing the above powder and Ag powder with a diameter of 20 to 100 μm, wherein the mass ratio of the Ag powder is 15%, and then placing the two powders in a powder mixer and mixing them evenly;

[0061] (3) The mixed powder was placed in a Φ10 mm graphite mold, and then sintered in a spark plasma sintering furnace with a sintering pressure of 30 MPa, a heating rate of 100 °C / min, a sintering temperature of 820 °C, and a sintering time of 5 min. After sintering, the mixture was cooled in the furnace;

[0062] (4) The surface of the sintered sample was polished and cleaned, then sealed in a glass tube with argon protection, heat treated at 850°C for 20 min, and then quenched in water.

[0063] Although the present invention is disclosed as above, the protection scope of the present invention is not limited thereto. Those skilled in the art can make various changes and modifications without departing from the spirit and scope of the present invention, and these changes and modifications will fall within the protection scope of the present invention.

Claims

1. A method for preparing a La-Fe-Si based magnetic refrigeration material, characterized in that: The following steps are involved: S1, mixing spherical La-Fe-Si based alloy powder and spherical Ag powder to obtain mixed powder; S2, sintering the mixed powder obtained in step S1 into a block; S3. Heat-treating the block obtained in step S2 to obtain a La-Fe-Si based magnetic refrigeration material.

2. The method for preparing the La-Fe-Si based magnetic refrigeration material according to claim 1, characterized in that: The method also includes step S0 of preparing La-Fe-Si based alloy powder by gas atomization method.

3. The method for preparing the La-Fe-Si based magnetic refrigeration material according to claim 1, characterized in that: In the step S1, the powder diameter of the La-Fe-Si based alloy powder is 0.1-100 μm, and the powder diameter of the Ag powder is 0.1-100 μm.

4. The method for preparing La-Fe-Si based magnetic refrigeration material according to claim 1, characterized in that: In the step S1, the mass proportion of Ag powder in the mixed powder is 5% to 20%.

5. The method for preparing the La-Fe-Si based magnetic refrigeration material according to any one of claims 1 to 4, characterized in that: In the step S2, the sintering method is spark plasma sintering.

6. The method for preparing the La-Fe-Si based magnetic refrigeration material according to claim 5, characterized in that: In the step S2, the sintering temperature is 650-850°C, the sintering time is 3-10 minutes, and the sintering pressure is 20-50 MPa.

7. The method for preparing the La-Fe-Si based magnetic refrigeration material according to any one of claims 1 to 4, characterized in that: In the step S3, the heat treatment is carried out under the protection of an inert atmosphere, the heat treatment temperature is 600 to 1000° C., and the heat treatment time is 5 min to 6 h.

8. The method for preparing La-Fe-Si based magnetic refrigeration material according to claim 1, characterized in that: The method further comprises step S4, wherein the material obtained in step S3 is subjected to hydrogenation treatment, the hydrogen pressure is 1 to 5 bar, the treatment temperature is 100 to 500° C., and the treatment time is 1 to 10 hours.

9. A La-Fe-Si based magnetic refrigeration material, characterized in that: The La-Fe-Si based magnetic refrigeration material is prepared by the preparation method according to any one of claims 1 to 8, wherein the La-Fe-Si particles in the microstructure are wrapped with Ag phase.